Can Modified Kurokawa's Double-Door Laminoplasty Reduce the Incidence of Axial Symptoms at Long-term Follow-up?. Issue 4 (May 2015) - Wang, Le; Wei, Fuxin; Liu, Shaoyu; Wan, Yong; Chen, Ningning; Cui, Shangbin; Zhong, Rui; Huang, Yangliang
<x xml:space="preserve">Abstract</x> Study Design: A prospective cohort study. Objective: The purpose of this study was to determine whether the modified procedure reduces long-term axial symptoms (AS) and to understand better why the AS occur. Summary of Background Data: Following Kurokawa's double-door laminoplasty, postoperative AS reduce the quality of life of patients with cervical spondylotic myelopathy. The etiology of AS remains unclear. Some studies report that preservation of the C7 spinous process can reduce the frequency of AS. The modified Kurokawa procedure prevents AS by preserving the semispinalis cervicis insertion in the spinous process of C2. However, it remains unclear whether the modified procedure lowers the incidence of AS in the long term (ie, >3 y). Materials and Methods: This prospective cohort study investigated preoperative and postoperative v, cervical intervertebral range of motion, postoperative neurological recovery, neck disability index, visual analog scale, surgical cost, and time and blood loss. Results: Both groups had satisfied improvement of neurological functions (P>0.05). At 3 months and 1 year after surgery, the difference in frequency between no symptoms and mild/severe symptoms was significant (traditional group, 39.06%; modified group, 20.45%) (P<0.05). Interestingly, 3 years after surgery, there were no significant between-group differences (P>0.05). Conclusions: This modified approach reduced the incidence of postoperative ASs at 3 months and 1 year after the operation; however, the between-group difference was not significantly different at the 3-year follow-up. The reason for this finding is unclear; it may indicate that the incidence of AS is caused by other factors, such as the preservation of the C7 spinous process rather than the C2 spinous process.